If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -16 = 16x + -18 Reorder the terms: -16 + 18x = 16x + -18 Reorder the terms: -16 + 18x = -18 + 16x Solving -16 + 18x = -18 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -16 + 18x + -16x = -18 + 16x + -16x Combine like terms: 18x + -16x = 2x -16 + 2x = -18 + 16x + -16x Combine like terms: 16x + -16x = 0 -16 + 2x = -18 + 0 -16 + 2x = -18 Add '16' to each side of the equation. -16 + 16 + 2x = -18 + 16 Combine like terms: -16 + 16 = 0 0 + 2x = -18 + 16 2x = -18 + 16 Combine like terms: -18 + 16 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| x+7+2x+19= | | 9-0p=3p-11 | | D-264=26 | | 9-op=3p-11 | | 2(5-y)/2=-4 | | 5t-4=3(t+2) | | 5.75t+6=14.5t+13 | | F-1=35 | | (2x-5)X^2+25=0 | | 4-6=3+4 | | 4/3•3.14•729000 | | -7=-0.5x-9 | | 2x^2-44x+242=0 | | cos(35)=7/x | | C-73=11 | | y=-0.5(-8)-9 | | D-155=19 | | -3=p/7=-5 | | 62000+2000x=55000+25000x | | 8x^2+69x+120=0 | | 6b-6-5=-23 | | x+6=4+12 | | 5(3(x-1))= | | 2/9x-1/3= | | Y=3/2-9 | | 5x+15-x=3(3x+5)+10 | | 6m+6n-4m+10n= | | (11/8k)-2-2(1/7)=(305/168) | | 24x=2x+14 | | 3-1/4y=2 | | 36+x=16+12 | | n+8(5-n)=89 |